La politique, une invention humaine ou divine?: La pensée de Protagoras et le regard platonicien - Gallego, Julian Alejandro (2016)
The article analyses the problem of the development of politics according to the way in which this issue is presented in the myth of Plato´s Protagoras. The perspective on the gods in this dialogue is compared with that provided by the Sisyphus fragment attributed to Critias, to consider the role of gods and humans in the deployment of technai and the art of politics. In addition, it is studied the persuasiveness linked to the use of myth both in Platonic discursive strategies and in the educational practices of the sophists. Finally, the possible Protagorean contents in this dialogue and their links with the conditions of the Athenian democracy during the fifth century B.C. are also considered.